Implementation of Quality Control to Overcome Defective Tile Production With the Application of Statistical Process Control (SPC) Methods - Luthfi Ikhsan Al Ghani; Isnaini Nurisusilawati; Ridho Ananda (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
One of the main factors to improve product quality is to carry out quality control. The purpose of this research is to reduce or suppress the number of defective tile products produced by controlling quality. The analytical method used in this research is Statistical Process Control (SPC) by calculating the percentage of damage to the product, CL, UCL, and LCL. The results of this study found that quality control in Super Soka Masinal Tile UKM was not controlled, this can be seen based on the calculation that there are 4 points outside the control limit so that the number of rejects exceeds the maximum allowable limit. And based on the Pareto diagram, it is known that the crack defect is the highest defect with a percentage of 44%. Therefore, it is necessary to propose improvements to crack defects using a fishbone diagram. Salah satu faktor utama untuk meningkatkan kualitas produk adalah dengan melakukan pengendalian kualitas. Tujuan pada penelitian ini adalah untuk mengurangi ataupun menekan jumlah pada produk cacat genteng yang dihasilkan dengan cara melakukan pengendaian kualitas. Metode analisis yang digunakan dalam penelitian ini adalah Statistical Process Control (SPC) dengan menghitung persentase kerusakan pada produk, CL, UCL, dan LCL. Hasil penelitian ini ditemukan bahwa pengendalian kualitas di UKM Genteng Super Soka Masinal tidak terkendali, ini dapat dilihat berdasarkan perhitungan terdapat 4 titik berada di luar batas kendali sehingga jumlah reject yang ada melebihi batas maksimal yang diperbolehkan. Dan berdasarkan diagram pareto, diketahui bahwa cacat retak merupakan cacat yang tertinggi dengan persentase 44%. Oleh karena itu perlu dilakukannya usulan perbaikan pada cacat retak dengan menggunakan fishbone diagram.